Resource allocation for non‐delay‐sensitive satellite services using adaptive coding and modulation–multiple‐input and multiple‐output–orthogonal frequency division multiplexing. Issue 3 (1st February 2016) - Mokari, Nader; Hajipour, Pedram; Mohammadi, Leila; Sardrood, Parvin Sojoodi; Kashani, Zahra Ghattan
Abstract : Nowadays, with the advent of new services, the need for high transmission data rates is inevitable. Thus, to solve this problem, the simultaneous use of multiple antennas at the transmitter and the receiver is mandatory. On the other hand, due to limited resources, their allocation is essential. To allocate resources in satellite systems, multiple‐input–multiple‐output, orthogonal frequency division multiple access, and adaptive coding and modulation techniques can be simultaneously applied. In this study, the resource allocation for non‐delay‐sensitive services is evaluated. The proposed optimisation problem is to maximise the sum data rate under the upward transmission power constraint. The authors solve the considered optimisation problem via the dual decomposition methods for both continuous and discrete cases. Finally, through simulation, the proposed algorithms are investigated and confirmed.